2011
DOI: 10.2298/bah1104705b
|View full text |Cite
|
Sign up to set email alerts
|

Welfare assessment of three chicken breeds (Gallus Gallus Domesticus) under different production systems

Abstract: The objective assessment of welfare in poultry under different rearing systems has gained an increasing importance. In particular, organic rearing systems are examined in relation to improving poultry welfare and the quality of poultry production at a worldwide scale. The aim of the present study was to assess the welfare of parent flocks-White Plymouth Rock, Barred Plymouth Rock (Line F) and New Hampshire, reared under two production systems-indoor on a litter and organic (sleep houses and walk yards). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The authors suggested that to ensure acceptable welfare and health in these broilers, it may be necessary to provide more opportunities for them to rest in an elevated position. Bozakova et al (2011) found that higher welfare of birds reared organically was linked to the greater number of birds spending their time dust bathing and preening, fewer episodes of aggressive behaviours, as well as lower plasma corticosterone levels, compared to birds reared indoor on litter. In stress tests, it was found that slow-growing bird strains (more commonly used in organic production systems) displayed a quicker reaction time when submitted to tonic immobility test, which implies less stress reaction (Castellini et al 2016).…”
Section: Behavioural Effectsmentioning
confidence: 96%
“…The authors suggested that to ensure acceptable welfare and health in these broilers, it may be necessary to provide more opportunities for them to rest in an elevated position. Bozakova et al (2011) found that higher welfare of birds reared organically was linked to the greater number of birds spending their time dust bathing and preening, fewer episodes of aggressive behaviours, as well as lower plasma corticosterone levels, compared to birds reared indoor on litter. In stress tests, it was found that slow-growing bird strains (more commonly used in organic production systems) displayed a quicker reaction time when submitted to tonic immobility test, which implies less stress reaction (Castellini et al 2016).…”
Section: Behavioural Effectsmentioning
confidence: 96%